Changes in circulating NK and innate-like T cells in type 1 and type 2 diabetes - Loguinova, Marina; Sergeev, Nikita; Samsonova, Margarita; Sorokina, Alyona; Grebennikov, Dmitry; Golodnikov, Ivan; Goncharenko, Anna; Bocharov, Gennady; Laptev, Dmitry; Khusainova, Rita; Minniakhmetov, Ildar; Shestakova, Marina; et al. (Frontiers in Immunology, 2025)
BackgroundInflammatory responses that accompany the progression of type 1 (T1D) and type 2 diabetes mellitus (T2D) are fundamentally distinct in their underlying nature. T1D is predominantly driven by autoimmune-mediated inflammation, whereas T2D is characterized by a chronic, low-grade metabolic inflammation. A growing body of evidence has highlighted the involvement of natural killer (NK) cells in pathophysiology of both forms of diabetes; nevertheless, the precise mechanisms and the roles played by specific NK cell subsets remain incompletely understood.MethodsMulticolor flow cytometry was used to identify several NK and innate-like T cell subpopulations in peripheral blood of patients with adult-onset T1D (n=23) and T2D (n=14) in comparison to healthy volunteers (n=24). Subset identification was based on expression of functional antigens (CD16 and CD56), co-receptors (CD8 and CD38), inhibitory receptors (NKG2A and CD161), and transcription factor EOMES. Quantitative analysis using Spearman’s rank correlation coefficients was performed to identify possible association between immune and clinical parameters and to rank the clinical parameters with respect to the number of connections with immune cell populations.ResultsT1D was accompanied by a reduction in overall NK cells and their dominant cytolytic CD56dimCD16bright subpopulation. Also a 50% increase in frequency of CD8+ NK cells was observed together with a growth of CD8+CD38+, CD8+CD161+, CD8+NKG2A+, and CD8+EOMES+ NK subsets. T2D was associated with a more than twofold decrease in the frequency of MAIT cell subset within CD8+ T cell population. Correlation analysis of the obtained data set revealed quantitative relationships between immune status parameters and clinical indicators, highlighting the involvement of NK cell subsets and innate-like T cells in shaping the phenotype of the pathological process and their complex role in regulating the immunopathogenesis of T1D and T2D.ConclusionIn this pilot study, we provide evidence that different subpopulations of NK cells and innate-like T cells are involved in the immunopathogenesis of T1D and T2D, through a decline in the control of immune reactivity in T1D, while sustaining chronic metainflammatory responses in T2D. A critical elevation of CD8+ NK cells was associated with T1D, while loss of circulating MAIT cells was a hallmark of T2D.